Factors influencing satisfaction and well-being among parents of congenital heart disease children: development of a conceptual model based on the literature review - Lawoko, Stephen (Scandinavian Journal of Caring Sciences, 2007)
The treatment and management of congenital heart disease (CHD) has improved dramatically over the past 25 years, necessitating re-evaluation of satisfaction with care and well-being among CHD children and their parents (PCCHD). The present study reviews the published literature over the past 25 years on parental satisfaction with the paediatric care of CHD and well-being among the parents, with the specific aim of: (a) assessing the extent of psychosocial problems and grade of satisfaction with care and (b) modelling factors associated with satisfaction and well-being among the parents. Results: There is general agreement in the literature that PCCHD experience psychosocial morbidity to a higher degree than parents of children with other paediatric conditions and parents of healthy children. The research on satisfaction with care among PCCHD is not conclusive, though there is considerable agreement that a substantial proportion of PCCHD may not be receiving adequate information regarding the ill-child’s condition, treatment and medical prognosis. Finally, based on the review of factors affecting satisfaction and well-being, a model is generated indicating that interactions between parental perception of CHD, psychosocial resources and social vulnerability may account for differences in well-being among PCCHD, which in turn may explain differences in satisfaction with care among them. Conclusion: A holistic approach to the care of CHD that acknowledges the role of parents’ perception of CHD, need for psychosocial resources and social vulnerability in the adaptation process is recommended to improve parental satisfaction with the care of CHD.
Keywords: Congenital heart disease; Parents; Satisfaction; Well-being; Psychosocial resources; Social vulnerability; Family health; Review